Analisis Kepuasan Mahasiswa UIN Semarang Terhadap E-Learning Menggunakan Algoritma C.45 - Bilqisth, Shona Chayy; Amalia, Farah (Universitas PGRI Semarang, 2022)
Student satisfaction on the use of e-learning is an important role for the continuity of an educational institution, especially in the current era of the covid 19 pandemic, the process of teaching and learning activities that are usually carried out in offline classes is abolished and replaced by utilizing the e-learning system. Because of the importance of the role of e-learning as a medium for student learning, knowledge is needed to determine the level of student satisfaction of e-learning as an evaluation material for managers to improve the quality of e-learning so that it can provide optimal services to students. Therefore, a classification technique with data mining is needed using the c.45 algorithm method on the WEKA (Waikato Environment for Knowledge Analysis) software. The results show that 73% of students are satisfied with the e-learning of the State Islamic University of Semarang and 23% of students are not satisfied with an accuracy of 84.76%.